Investigating the status and influencing factors of professional identity formation among Chinese medical interns: a mixed methods study - Xuedong Jia; Jiayi Du; Tianyu Xu; Xuejun Yin; Qiufang Zhang; Xiaoyue Bao; Wan Zhang; Shuzhang Du; Youhong Hu; Loraine Cook; Zhimin Chen; Zhao Yin (BMC Medical Education)
Abstract Background Professional Identity Formation (PIF) involves a movement through a series of conceptually distinct developmental stages. Kegan’s theory of PIF is divided into 6 phases (stages 0–5). It is believed that students undergo stages 2–4 (imperial, interpersonal, institutional) during medical education. Currently, the PIF of medical interns is being extensively studied. However, few studies on Chinese interns. Social-ecological theory (STC) suggests that an individual’s behavior and development are shaped by his or her multilevel interactions with the environment, so it’s necessary to explore the mechanisms of interns’ PIF within Chinese socio-cultural settings. Aim This study assesses the PIF status of Chinese medical interns and investigates interactions between multidimensional influencing factors underlining the process of PIF. Methods This is a convergent mixed methods case study and consists of two parallel parts. The quantitative research involved a cross-sectional survey using online questionnaires on PIF, job burnout, and resilience. Four stage-specific scales (SASs) and a development scale (DS) were used to quantify the complexity and divergent processes of PIF. In the qualitative research, authors arranged semi-structured face-to-face interviews with medical interns. Data collection and analysis were conducted simultaneously. The model of Reciprocal Determinism is used as theoretical framework until data saturation was achieved. Results A total of 1054 responses were considered valid. Interns’ score of stage 4-specific attribute scale (SAS-4) scoring significantly higher than other SASs. Gender, higher family income, receiving scholarships, having continuous mentor guidance, and having clear career plans were identified factors that influences different stages of intern’s PIF. Seven themes that influence PIF were identified from the qualitative research. The interplays between personal, behavioral, and environmental factors are bidirectional and complex. The Balancing of these complex relationships is identified as a crucial factor in PIF. Conclusion This study illustrates that Chinese medical interns were at stage 4 according to Kegan’s model. Additionally, the reciprocal interactions between personal, behavioral, and environmental aspects can serve as potential mechanisms for PIF.